An Analysis of Quantifier Scope Restrictions in Dependence Logic - Naumann, Ralf; Petersen, Wiebke (Proceedings of the Amsterdam Colloquium, 2013)
In our contribution we will present a strictly semantic approach to scope phenomena which is based on (Dynamic) Dependence Logic (DL) [Vaa07, Gal13] and ideas from Dynamic Semantics [Fer93]. Formulas as well as quantifiers are interpreted as relations between sets of assignments. Scopal ambiguities are analyzed as a form of non-determinism: processing a formula in an input context X can lead to different output contexts Y . These outputs are constraint by imposing dependence relations on Y .1